Development of attractants and repellents for Tuta absoluta based on plant volatiles from tomato and eggplant - Chen, Tingting; Chen, Limin; Wang, Jinchao; Cheng, Jianghui; Yi, Songwang; Hafeez, Muhammad; Zhou, Shuxing; Li, Yuanxi; Li, Xiaowei; Lu, Yaobin (Frontiers in Sustainable Food Systems, 2023)
Introduction Tuta absoluta is currently considered one of the most devastating invasive pests of solanaceous plants worldwide, causing severe damage to the tomato industry. Insects use volatile organic compounds (VOCs) to locate host plant for feeding and oviposition. Those VOCs could be developed as lures for pest monitoring and control. Methods In this study, the differentially accumulated VOCs between the preferred host (tomato) and non-preferred host (eggplant) were analyzed by GC–MS method, and their roles on female T. absoluta host selection and egg laying behaviors were investigated using electroantennography (EAG), olfactometer and cage experiments. Results A total of 39 differentially accumulated VOCs were identified in tomato and eggplant. Strong EAG signals were obtained in 9 VOCs, including 5 VOCs highly accumulated in tomato and 4 VOCs highly accumulated in eggplant. Further olfactometer bioassays showed that 4 compounds (1-nonanol, ethyl heptanoate, ethyl octanoate and o-nitrophenol) were attractive to T. absoluta females, while 5 compounds (2-phenylethanol, 2-pentylfuran, trans,trans-2,4-nonadienal, 2-ethyl-5-methylpyrazine and trans-2-nonenal) were repellent, indicating that VOCs from host plants play important roles in host plant preferences. The attractive activities of 1-nonanol and ethyl octanoate, as well as the repellent activities of trans,trans-2,4-nonadienal and trans-2-nonenal, were further confirmed in cage experiments. Discussion In this study, two attractants and two repellents for T. absoluta were developed from plant released VOCs. Our results could be useful to enhance the development of eco-friendly and sustainable pest management strategies for T. absoluta.